Evaluating the knowledge, attitude, and practice of oncology nurses towards the safe handling of anti-neoplastic drugs - Albeah, Ali Mohammed (International Journal of Research in Medical Sciences, 2025)
Background: Safe handling of anti-neoplastic drugs (ADs) is critical for oncology nurses due to the potential health risks of occupational exposure. Occupational exposure to antineoplastic agents and safe handling of cytotoxic drugs (CDs) had gained a high concern among oncology nursing staff due to their potential health risks. This study evaluates the knowledge, attitude and practices (KAP) of oncology nurses towards the safe handling of these drugs at King Abdullah Medical City, Makkah, Saudi Arabia. Methods: A cross-sectional survey was conducted among 88 oncology nurses across oncology, hematology, and chemotherapy units using a validated questionnaire. Results: Results showed that nurses demonstrated good knowledge regarding cytotoxicity, correct use of personal protective equipment (PPE), and waste disposal methods but reported gaps in the use of biological safety cabinets (BSC). Attitudes reflected adherence to safety guidelines but highlighted challenges during work overload. Practices revealed strengths in BSC usage but weaknesses in consistent PPE use and incident reporting. A strong correlation was observed among KAP variables and safe handling practices. Conclusions: The safe handling of cytotoxic medications is a crucial feature, and nurses can avoid issues for both themselves and their patients. Overall, the nurses reported good practices for handling CDs safely, however a significant number of the nurses still have fair and negative habits. Effective actions are required to improve the procedures followed by oncology nurses when handling cytotoxic medications safely.